Role of Staphylococcus aureus coagulase and clumping factor in pathogenesis of experimental endocarditis - FOSTER, TIMOTHY (My University, 1995)
The pathogenic role of staphylococcal coagulase and clumping factor was investigated in the rat model of endocarditis. The coagulase-producing and clumping factor-producing parent strain Staphylococcus aureus Newman and a series of mutants defective in either coagulase, clumping factor, or both were tested for their ability (i) to attach in vitro to either rat fibrinogen or platelet-fibrin clots and (ii) to produce endocarditis in rats with catheter-induced aortic vegetations. In vitro, the clumping factor-defective mutants were up to 100 times less able than the wild type strain to attach to fibrinogen and also significantly less adherent than the parents to platelet-fibrin clots. Coagulase-defective mutants, in contrast, were not altered in their in vitro adherence phenotype. The rate of in vivo infection was inoculum dependent. Clumping factor-defective mutants produced ca. 50% less endocarditis than the parent organisms when injected at inoculum sizes infecting, respectively, 40 and 80% (ID40 and ID80, respectively) of rats with the wild-type strain. This was a trend at the ID40 but was statistically significant at the ID80 (P < 0.05). Coagulase-defective bacteria were not affected in their infectivity. Complementation of a clumping factor-defective mutant with a copy of the wild-type clumping factor gene restored both its in vitro adherence and its in vivo infectivity. These results show that clumping factor plays a specific role in the pathogenesis of S. aureus endocarditis. Nevertheless, the rate of endocarditis with clumping factor-defective mutants increased with larger inocula, indicating the contribution of additional pathogenic determinants in the infective process.